Sosialisasi Penegakan Hukum Angkutan di Kabupaten Kolaka Utara sebagai Upaya Mendorong Kepatuhan Pengemudi - Syaiful; Ringo Taufan Laode; Rina Sutriana; Maudhy Satyadharma; Neni Susanti; Hado; Galih Adi Sulistyo; Mahdar; Ahiula; Muhammad Faza Almaliki (J-Abdimas Cenderawasih, 2025)
The discipline and compliance of public transportation drivers are crucial factors in ensuring safe, comfortable, and secure transportation. North Kolaka Regency, as one of the entry and exit points to Southeast Sulawesi Province, with its high volume of goods and people, faces various challenges related to administrative violations, vehicle roadworthiness, and compliance with transportation laws. This community service initiative aims to improve drivers' and transportation business owners' understanding of the importance of implementing regulations, licensing procedures, and applicable legal sanctions through outreach, direct education, enforcement, supervision, and law enforcement. The activities included problem mapping, outreach, outreach, education, and evaluation of drivers' perceptions and understanding. The results of the initiative indicate an increase in drivers' knowledge of law enforcement provisions and their awareness of complying with technical and administrative transportation requirements.